If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y + 4 = 0 Reorder the terms: 4 + 2x + -1y = 0 Solving 4 + 2x + -1y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 2x + -4 + -1y = 0 + -4 Reorder the terms: 4 + -4 + 2x + -1y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2x + -1y = 0 + -4 2x + -1y = 0 + -4 Combine like terms: 0 + -4 = -4 2x + -1y = -4 Add 'y' to each side of the equation. 2x + -1y + y = -4 + y Combine like terms: -1y + y = 0 2x + 0 = -4 + y 2x = -4 + y Divide each side by '2'. x = -2 + 0.5y Simplifying x = -2 + 0.5y
| 14m^2-9m^3= | | 5x+4x+1=0 | | 5x+4x+1=x | | r+10=19 | | 7x+2y+3z=42 | | -18.437=-1.3(8-m) | | 14x+13=13x+4 | | 4(y+7)=9y+43 | | 6(y+9)=8y+54 | | 3x-6=10+2x | | (2x+3)-(-6x+5)= | | y=-1+1 | | 43-3x=6x+19 | | 4x*2+9x-27=102 | | 1+3x=21-x | | 11-9x=37-16x | | -14-3x=10x-9 | | -9(7)=-63 | | x=y+z+2 | | 3x(2x+x^17)= | | abx=-c | | x-b+a=c | | -34-x=6-10x | | -15+25(21)=6+24(21) | | 7x+21=7x-21 | | X^3+7x^2+2x+14=0 | | 3x^2-1x-14=0 | | 15s^2-40s=0 | | 9(-9)+2=8(-9)-7 | | 0.05+0.12(x+5000)=940 | | 5x-3x=15 | | 10c(d+4c+7)= |